Creative reflections on brainstorming (UCL Press, 2012)
Brainstorming is the default method of idea-generation in organisations, and is widely applied in higher education by students, academics and support staff. Its popularity is mainly attributable to an illusory belief that groups working together are more productive than individuals working apart. Shared responsibility, the need for collaboration and the social dimension to work also sustains the popularity of brainstorming. To add further insight to the numerous studies that have been demonstrated the inefficiencies of brainstorming, this paper describes preliminary results on participants' self-reflection during a brainstorm. Recommendations are made for improving the productivity of group brainstorms.